Fungsi Kognitif Skala MOCA-INA pada Peserta PPDS Anestesiologi dan Terapi Intensif: Perbandingan Sebelum dan Setelah Jaga di Rumah Sakit - Wonggo, Tesalonika; Kambey, Barry I.; Lalenoh, Diana C. (Medical Scope Journal, 2025)
Abstract: Shift duty can negatively impact cognitive function among residents of Specialist Program. This study aimed to obtain the differences in cognitive function of Anesthesiology and Intensive Therapy (ATI) residents at Universitas Sam Ratulangi before and after on-call duty at Prof. Dr. R. D. Kandou General Hospital Manado. This was a descriptive observational study with a cross-sectional design. Samples were residents of ATI who completed the Indonesian version of the Montreal Cognitive Assessment (MoCA-INA) before and 24 hours after on-call duty. The results showed a total of 31 residents as samples with a proportion of 24 (77.4%) males and seven (22.6%) females. There was a decline in most cognitive domains, with a statistical analysis demonstrating a decrease in the mean MoCA-INA score from 26.8387 to 25.0000, accompanied by a p-value of 0.000 (<0.05) and a Z-score < -2 obtained from the Wilcoxon test. In conclusion, there is a significant difference in cognitive function of residents of Anesthesiology and Intensive Therapy Specialist Program of Universitas Sam Ratulangi before and after on-call duty at the hospital. This is possibly due to cognitive overload caused by the shift duty. Keywords: cognitive function; MoCA-INA; shift duty; specialist program   Abstrak: Tugas jaga yang berat dapat berdampak negatif terhadap fungsi kognitif peserta Program Pendidikan Dokter Spesialis (PPDS). Penelitian ini bertujuan melihat perbedaan fungsi kognitif PPDS Anestesiologi dan Terapi Intensif (ATI) Universitas Sam Ratulangi sebelum dan sesudah jaga di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong-lintang pada PPDS ATI yang mengisi Montreal Cognitive Assesment versi Indonesia (MoCA-INA) sebelum dan 24 jam setelah jaga. Penelitian ini bertujuan untuk mengidentifikasi apakah terdapat perbandingan antara fungsi kognitif pada PPDS sebelum dan setelah menjalani tugas jaga 24 jam. Hasil penelitian mendapatkan 31 sampel dengan proporsi laki-laki sebanyak 24 (77,4%) orang dan perempuan sebanyak tujuh (22,6%) orang. Penurunan pada sebagian besar domain kognitif dengan hasil analisis statistik menunjukkan penurunan rerata skor MoCA-INA dari 26,8387 menjadi 25,0000 disertai dengan nilai p<0,05 (p=0,000) dan Z-score <-2 yang diperoleh melalui uji Wilcoxon. Simpulan penelitian ini ialah terdapat perbedaan fungsi kognitif PPDS Anestesiologi dan Terapi Intensif Universitas Sam Ratulangi yang bermakna antara sebelum dan setelah jaga di rumah sakit. Hal ini diduga disebabkan kelebihan beban kognitif akibat tugas jaga. Kata kunci: fungsi kognitif; MoCA-INA; tugas jaga; residen pendidikan dokter spesialis